Sistem Monitoring Automated Weather Observing System (AWOS) Berbasis Android Studi Kasus BMKG Sultan Mahmud Badaruddin II Palembang - Wynda Anggraeni Iskandar; Lindawati Lindawati; Mohammad Fadhli (SMATIKA JURNAL : STIKI Informatika Jurnal, 2021)
Weather is a condition of the air in a place in a short time taken from the results of measurements of weather parameters. In survival, weather conditions play a very important role in all activities. One of the activities that are highly dependent on weather conditions is aviation activities. So in this paper, a monitoring system is designed to monitor the measurement results from the Automated Weather Observing System (AWOS) or an automatic weather monitoring tool used to monitor the current weather intended for flights at Sultan Mahmud Badaruddin II Airport Palembang. In this study, the Automated Weather Observing System (AWOS) Monitoring System will be made an android-based website (mobile web) so that it is possible for users to access it anytime and anywhere. The design of this monitoring system uses the SDLC (System Development Life Cycle) method, which is an android-based web development system that adds or changes some of the existing systems. This mobile web will display measurement results from the Automated Weather Observing System (AWOS) and is designed to make it easier for BMKG observers to observe the current weather, whether it is stable or experiencing drastic weather changes. If the graph displayed in this application undergoes a significant change, this application will send a notification to e-mail regarding the current weather conditions.